2005
DOI: 10.1007/s10646-004-6265-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Hg Bioaccumulation and Transfer in Aquatic Food Webs Across Multi-lake Studies in the Northeast US

Abstract: The northeastern USA receives some of the highest levels of atmospheric mercury deposition of any region in North America. Moreover, fish from many lakes in this region carry Hg burdens that present health risks to both human and wildlife consumers. The overarching goal of this study was to identify the attributes of lakes in this region that are most likely associated with high Hg burdens in fish. To accomplish this, we compared data collected in four separate multi-lake studies. Correlations among Hg in fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 48 publications
10
108
3
3
Order By: Relevance
“…The MeHg concentration of large midges and dragonflies were not affected by nutrient additions, whereas MeHg concentrations in small midges were enhanced by nutrient additions. In several large field surveys, the concentration of MeHg in biota has been inversely correlated with various measures of trophic state and primary production [13,[34][35][36][37] Table S1. When a significant Nutrient  Fish interaction (N  F) was detected, we tested for simple main effects.…”
Section: Discussionmentioning
confidence: 99%
“…The MeHg concentration of large midges and dragonflies were not affected by nutrient additions, whereas MeHg concentrations in small midges were enhanced by nutrient additions. In several large field surveys, the concentration of MeHg in biota has been inversely correlated with various measures of trophic state and primary production [13,[34][35][36][37] Table S1. When a significant Nutrient  Fish interaction (N  F) was detected, we tested for simple main effects.…”
Section: Discussionmentioning
confidence: 99%
“…Two coal combustion power plants are also located in the southern portion of NH and are likely contributors to the local atmospheric load of Hg. Within the waterways of the Northeastern United States, including NH, biological species have been identified as containing elevated Hg levels (Chen et al, 2005;Evers et al, 2007) with atmospheric deposition considered the dominant source in undisturbed watersheds (Chen et al, 2005). Three MDN sites were previously located in NH with sample collection lasting from 7 to 16 months and the most recent sampling terminated in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found a positive correlation between the relative availability of N and P and fish mercury concentrations from hundreds of lakes (14,15). High availability of P relative to N (i.e., low N:P) results in a low algal N:P ratio (indicative of high algal quality as food), causing rapid growth in zooplankton, particularly Daphnia (4,16).…”
mentioning
confidence: 99%